Concomitant presence of bilateral nevus of Ota with unilateral nevus of Ito and halo nevus: a rare association - Salunke, Aarti S.; Nagargoje, Mahendra V.; Chavan, Ravindranath B.; Bansal, Nilima M. (International Journal of Research in Dermatology, 2017)
Nevus of Ota is dermal melanocytosis, generally presents as blue-black or gray-brown patchy diffuse pigmentation. Most commonly occurs unilaterally on face in areas innervated by the first and second divisions of trigeminal nerves. Bilateral involvement and oral mucosal involvement can occur, but as a rare manifestation. Nevus of Ota may be very rarely associated with the nevus of Ito and other extra cutaneous features. The halo nevus may be seen in congenital or acquired melanocytic nevi. Presence of halo nevus in conjunction with two different dermal nevi is not reported till date. We are reporting 19 year old female presented with bilateral Nevus of Ota with oral mucosal involvement and associated nevus of Ito and halo nevus.